The Effect of Price Fairness, F&B Product Quality, and Physical Environment Quality on Satisfaction and Their Impact on Repurchase Intention and Recommendation Intention - Syamsuryo Arjuna; Kadarisman Hidayat; Yusri Abdillah (PT. Global Research Collaboration, 2026)
This study investigates the influence of price fairness, F&B product quality, and physical environment quality on customer satisfaction, as well as their effects on repurchase intention and recommendation intention in the context of CW Coffee & Eatery. The increasing competition in the coffee shop industry highlights the importance of understanding factors that drive customer loyalty and positive behavioral outcomes. A quantitative explanatory approach was applied using data from 384 respondents selected through non-probability sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM) to examine the relationships among variables and test both direct and indirect effects. The results show that price fairness, product quality, and physical environment quality each have a significant positive effect on customer satisfaction. In addition, all three variables significantly influence both repurchase intention and recommendation intention. Customer satisfaction is also found to significantly mediate all relationships between the antecedent variables and behavioral intentions, indicating partial mediation effects. These findings imply that customer loyalty in coffee shop settings is shaped by both direct perceptions of service attributes and indirect effects through satisfaction as a psychological mechanism. Practically, maintaining fair pricing, consistent product quality, and a comfortable physical environment is essential to strengthen both repurchase behavior and word-of-mouth intention. The originality of this study lies in the integrated model that simultaneously examines three experiential factors and their dual effects on repurchase intention and recommendation intention through customer satisfaction in a single coffee shop context.